Profitability and sustainability of modern fish farming in Benin: An on-farm experimental appraisal of two production systems of Clarias gariepinus - Honfoga, Barthelemy G.; Tognon, Isabelle A.; CHIKOU, ANTOINE (My University, 2017)
An on-farm experimental appraisal was done to compare the profitability of two production systems of Clarias gariepinus in Benin, and to assess the challenges of modern fish farming in West Africa. The results showed that fish farming using above ground tanks (AGT) was not profitable enough to reward production and recover capital costs, should the investments be fully bank loan-funded. At present feed prices, it cannot cost-effectively meet the market demand, and can only provide proteins to producers’ households for their own consumption. On the contrary, Lake Water-fed Pond (LWP) fish farming of Clarias gariepinus was ten-fold more profitable (profit rate of 57.7%) than AGTs. Although, its profit rate is still far below the potential performance level in the sub-region, it should be promoted among Lake Village cooperatives or young rural entrepreneurs to meet the growing fish demand, especially from Nigeria. Therefore, financial support should be made available to face the high costs of initial investments. Likewise, considering their lower investment costs, AGTs can also be promoted among urban farmers, only if cost-effective local substitutes to imported feeds become available. There is a need to install quality feed production enterprises to promote both fish production systems towards sustainability, food security and economic development.
Keywords: Modern fish farming; lake water-fed ponds; above-ground tanks; Clarias gariepinus; profitability; sustainability.